El espermatozoide criopreservado bovino es capaz de modular su requerimiento energético dependiendo de los sustratos oxidativos disponibles para la capacitación inducida in vitro con heparina - Fernández, S. (2014)
The aim of this investigation was to study in cryopreserved bovine sperm the requirements of oxidative substrates during heparin-induced capacitation. Percentages of capacitated sperm and viability and acrosome integrity were evaluated by chlortetracycline epifluorescent technique and Trypan blue stain/DIC, respectively and lactate concentration changes in the incubation medium were registered spectrophotometrically and cellular oxygen consumption polarographically, in the presence of lactate and/or pyruvate as oxidative substrates. Percentages of capacitated spermatozoa incubated with heparin and lactate/pyruvate or pyruvate as oxidative substrates were significantly higher compared to the other treatments. The viability and acrosomal integrity significantly decreased in the absence of substrates in all treatments. In heparin capacitated sperm in the presence of lactate/pyruvate, oxygen consumption was significantly higher compared to the other treatments. Lactate concentration in the incubation medium, in the presence of lactate or lactate/pyruvate and heparin, showed a decrease respect to control. The combination of oxidative substrates lactate/pyruvate is the best option to maintain sperm viability, respiratory burst and produce a high percentage of capacitated sperm, ensuring an active metabolism inthe gamete to cover the energy requirements of capacitation.